2023
DOI: 10.1002/adma.202210517
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibroin and Sericin Differentially Potentiate the Paracrine and Regenerative Functions of Stem Cells Through Multiomics Analysis

Abstract: emerging as a potential alternative to these problems. The tissue engineering triad involves the effective integration of cells, scaffolds, and signals for the development of biological substitutes to restore, maintain, and replace injured tissues and organs. [2] The scaffold plays a substantial role in the field of tissue engineering, primarily by providing physical support (structures and substrates) for cells to attach and grow, subsequently resulting in tissue formation. [3] A variety of natural and synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 131 publications
0
22
0
Order By: Relevance
“…Two other proteins (sericin and transferrin) were employed to fabricate UNP nanoparticles and similar trends of size changes and stability were observed, indicating the versatility of the UNP nanoparticle assembly strategy (Figure S2). 29,30 Subsequently, we assessed the crucial role of TA in promoting protein assembly. To remove the excess free TA in the solution, the UNP nanoparticle was dialyzed with the molecular weight cutoff at 14 kDa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other proteins (sericin and transferrin) were employed to fabricate UNP nanoparticles and similar trends of size changes and stability were observed, indicating the versatility of the UNP nanoparticle assembly strategy (Figure S2). 29,30 Subsequently, we assessed the crucial role of TA in promoting protein assembly. To remove the excess free TA in the solution, the UNP nanoparticle was dialyzed with the molecular weight cutoff at 14 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…Two other proteins (sericin and transferrin) were employed to fabricate UNP nanoparticles and similar trends of size changes and stability were observed, indicating the versatility of the UNP nanoparticle assembly strategy (Figure S2). , …”
Section: Resultsmentioning
confidence: 99%
“…However, mesenchymal stem cell respond differently to fibroin and sericin as observed by Zhang et al They found that fibroin had better effects on the immune system compared with sericin, suggesting it has more potential as a material for carrying mesenchymal stem cells in skin regeneration treatments. In a similar study, Tao et al developed a sericin/poly­(vinyl alcohol) based hydrogel as a drug delivery carrier for wound healing purposes.…”
Section: Applications Of Sericin As a Functional Biomaterialsmentioning
confidence: 91%
“…Inspired by these unique molecules, resulting diverse protein materials, such as spider silk, elastin, collagen, and mussel proteins, are favored in multiple industries. 5 For example, spider silk protein materials have been utilized for supertough electro-tendon 6 and cardiac tissue engineering 7 due to the extraordinary mechanical properties and biological features. However, the preparation of protein materials remains far behind the increasing demands.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins are accurately synthesized from 20 amino acid monomers, forming materials with precise structures and versatile functionalities by subsequent supramolecular self-assembly to realize their biological roles. Inspired by these unique molecules, resulting diverse protein materials, such as spider silk, elastin, collagen, and mussel proteins, are favored in multiple industries . For example, spider silk protein materials have been utilized for supertough electro-tendon and cardiac tissue engineering due to the extraordinary mechanical properties and biological features.…”
Section: Introductionmentioning
confidence: 99%